Clinical factors affecting cerebral oxygenation in patients undergoing peritoneal dialysis. Issue 11 (November 2021) - Kitano, Taisuke; Ito, Kiyonori; Ookawara, Susumu; Hoshino, Taro; Hayasaka, Hideyuki; Kofuji, Masaya; Uchida, Takayuki; Morino, Junki; Minato, Saori; Kaneko, Shohei; Yanai, Katsunori; Mutsuyoshi, Yuko; et al.
Background: Although cerebral regional oxygen saturation (rSO2 ) is significantly lower in hemodialysis (HD) patients than that in healthy controls, investigations on cerebral oxygenation in peritoneal dialysis (PD) patients are limited. We aimed to confirm the cerebral oxygenation status and identify the factors affecting cerebral rSO2 in PD patients. Methods: Thirty-six PD patients (21 men and 15 women; mean age, 62.8 ± 12.7 years) were recruited. In addition, 27 healthy volunteers (17 men and 10 women; mean age, 43.5 ± 18.8 years) were recruited as a control group. Cerebral rSO2 was monitored at the forehead using an INVOS 5100c oxygen saturation monitor. Results: Cerebral rSO2 was significantly lower in PD patients than that in healthy controls (57.0 ± 7.3% vs 68.9 ± 8.6%, p  < 0.001); moreover, cerebral rSO2 was significantly correlated with natural logarithm (Ln)-PD duration ( r  = −0.389, p  = 0.019) and serum albumin concentration ( r  = 0.370, p  = 0.026) in a simple linear regression analysis. Multivariable linear regression analysis was performed using variables that showed a significant correlation and p  < 0.20 (serum creatinine, serum sodium, Ln-C-reactive protein, and dosage of erythropoiesis-stimulating agent) with the cerebral rSO2 . Cerebral rSO2 was independently associated with Ln-PD duration (standardized coefficient: −0.339) and serum albumin concentration (standardized coefficient: 0.316). Conclusions: Cerebral rSO2 was significantly affected by the PD duration and serum albumin concentration. Further prospective studies are needed to clarify whether preventing a decrease in serum albumin concentration leads to the maintenance of cerebral oxygenation in patients undergoing PD.